High Harmonic Generation with Twisted Electrons - Gemsheim, Sebastian; Jan-Michael Rost (arXiv.org, 2019)
We present analytically and numerically the spectrum of high harmonic emission generated by twisted electrons in the presence of linearly polarized light. Ensuing transitions from electronic continuum states with orbital angular momentum to bound states give rise to circularly polarized attosecond pulses. For central collisions with twisted wavepackets continuum-bound transitions are subject to dipole selection rules. For non-central collisions a crossover from circularly to linearly polarized emission occurs for increasing impact parameter, due to the transverse topology of twisted wavepackets.